Media legacy of Shokan Ualikhanov during the period of development of Kazakh journalism - Sailaukyzy, A.; Azerbay, Ә.; Adilzhan, Ә. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2025)
This article examines the journalistic legacy of ShoqanUalikhanov through the lens of contemporary academic analysis. The study explores his contributions to the formation of national journalism during its developmental phase, his role in advancing Kazakh democratic public discourse, and the significance and forms of his media heritage, which exhibit characteristics of travel journalism. Additionally, public perceptions of his journalistic image are analyzed based on data from a social study. The findings of the scientific analysis demonstrate that even in his time, Shoqan Walikhanov adhered to principles characteristic of modern journalism, such as information analysis, fact-based research, and objective reporting. By applying the historical-comparative method, textual analysis, and source evaluation, his travel notes and ethnographic works are examined, revealing the presence of travel journalism elements. Furthermore, his journalistic contributions played a pivotal role in fostering Kazakh intellectual and democratic thought, introducing diverse journalistic formats, and incorporating visual storytelling through illustrations. Thus, Ualikhanov’s works can be regarded as one of the earliest domestic examples of travel journalism, underscoring their significance in the history of the national press. This, in turn, strengthens the academic foundation for studying the evolution of professional Kazakh journalism.